Complete EPR spectrum of the S3-state of the oxygen-evolving photosystem II. - Boussac,A; Sugiura,M; Rutherford,AW; Dorlet,P (J Am Chem Soc, 2009)
Despite crystallographic structures now available and intensive work in the past decades, little is known about the higher redox states of the catalytic cycle of Photosystem II, the enzyme responsible for the presence of O(2) on Earth and at the beginning of the process that has produced both the biomass and the fossil fuels. In one of the highest oxidation states, the S(3)-state, only signals at g-values higher than 4 have been detected so far at the X-band. In this work, we report for the first time the complete X-band EPR spectrum for the S(3)-state of Photosystem II. Simulations show that, for a spin state S = 1, as was previously suggested for S(3), it is not possible to account for all the features observed. A satisfactory simulated spectrum was obtained for a spin state S = 3 with zero-field splitting parameters D = 0.175 cm(-1) and E/D = 0.275. The detection of the full EPR signal for S(3) opens the door for new investigations and a better understanding of the catalytic cycle of Photosystem II.